Report 1972-73 - Planning Commission (Planning Commission, 1973)
This report provides a comprehensive overview of the activities and developments in the field of statistics in India during the early 1970s. It details the formation and meetings of various committees and advisory groups focused on improving statistical methodologies, training, and data collection processes. The text highlights the collaboration between national and international agencies, the establishment of the National Sample Survey Organisation, and the advancements in data processing through the Computer Centre. It also discusses the publications and statistical data supplied to international organizations, reflecting the ongoing efforts to enhance the quality and availability of statistical information for planning and policy formulation.
Government of India (Bharat Sarkar) Ministry of Planning (Yojna Mantraralya) Department of Statistics
Government of India (Bharat Sarkar) Ministry of Planning (Yojna Mantraralya) Department of Statistics
Keywords: Statistical Methodology; National Sample Survey Organisation; Data Processing; Advisory Committee; Consumer Price Index; Training in Statistics; International Collaboration; Statistical Publications; Economic Analysis Division; Statistical Abstracts